GIS Supported Evaluation of Surface Level Impacts Due to Abandoned Near?Surface Mine Locations - Alexander Kattner (International Conference on Ground Control in Mining, 2011)
Surface fractures in urbanized areas show the risk potential of near-surface mining. This kind of mining subsidence damage occurs mainly in areas where hard coal was mined near the surface with very little overlying rock strata. In North Rhine-Westphalia (NRW), the mining authorities assess areas that are at risk for caveins by means of envelopes constructed according to Hollmann and Nürenberg (1972). Drafting abandoned underground structures depends on the assessment of historical documents such as mine plans, mine titles, and operation plans of prior mines in this area. A research and development project establishing a comprehensive Geo Information System (GIS) for hazard prevention was undertaken in cooperation with the mining authorities of NRW. It aims to display the areas endangered by abandoned, shallow underground mines for the purpose of hazard prevention. A tool was programmed using ArcGIS as a result of this project. It is used to digitize underground workings from preserved mine plans, calculate outcrop lines of coal seams and display hazardous areas. In the future, a database of shallow mine workings will be established. The tool will be used for a systematical mapping of shallow workings and assessment of endangered areas.